Flexible heating film material containing nanocarbon and preparation method thereof

By adding nanocarbon powder to the resin material and processing it with a twin screw machine, the problem of lack of heating performance in the film in the prior art is solved, and a flexible heating film material with heating performance is prepared, and the use of modified nanocarbon powder further improves the heating performance and gas barrier properties of the material.

CN119708572AInactive Publication Date: 2025-03-28TIANNAI TECHNOLOGY (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411966688.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, films prepared with polyvinyl chloride, polyethylene, polypropylene and polystyrene as raw materials lack heating performance and are difficult to meet application scenarios with heating needs.

Method used

Nanocarbon powder was added to the resin material, and the flexible heating film material was prepared by melt extrusion by twin screw machine. The specific steps include mixing the resin material with the nanocarbon powder evenly, and then processing it through a twin screw machine to obtain a flexible heating film material containing nanocarbon.

Benefits of technology

By adding nanocarbon powder to the resin material, the obtained flexible heating film material containing nanocarbon has heating properties, and the addition of modified nanocarbon powder can further improve the heating performance and gas barrier properties compared with unmodified nanocarbon powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218526630000051
    Figure BDA0005218526630000051
  • Figure BDA0005218526630000061
    Figure BDA0005218526630000061
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of high polymer materials, and particularly discloses a flexible heating film material containing nanocarbon and a preparation method of the flexible heating film material. The preparation method of the nano-carbon-containing flexible heating film material comprises the following steps: uniformly mixing a resin material and nano-carbon powder, and performing melt extrusion through a twin-screw extruder to obtain the nano-carbon-containing flexible heating film material, the resin material is selected from one or a combination of more than one of polyvinyl chloride, polyethylene, polypropylene and polystyrene; the weight ratio of the resin material to the nano carbon powder is 10: (2-5). Research shows that the flexible heating film material containing nanocarbon prepared by the method has a heating function after being electrified; the application scene of the plastic film is widened, and the film prepared by taking the resin material as the raw material can be applied to the field with heating requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material preparation, and in particular to a flexible heating film material containing nano-carbon and a preparation method thereof. Background Art

[0002] Film is a thin, soft and transparent sheet; usually made of plastic, adhesive, rubber or other materials; it includes plastic film, composite film, superconducting film, optical film, etc., and is widely used in home appliances, medical, agriculture, industrial packaging and other fields.

[0003] Polyvinyl chloride, polyethylene, polypropylene and polystyrene are commonly used plastics for preparing films; however, the films prepared by the prior art using polyvinyl chloride, polyethylene, polypropylene and polystyrene as raw materials do not have heat generation properties and need to be further improved. Summary of the invention

[0004] In order to overcome at least one of the technical problems existing in the prior art, the present invention provides a flexible heating film material containing nano-carbon and a preparation method thereof.

[0005] The present invention first provides a method for preparing a flexible heating film material containing nano-carbon, which comprises the following steps: mixing a resin material and nano-carbon powder evenly, and then melt-extruding the mixture through a twin-screw extruder to obtain the flexible heating film material containing nano-carbon;

[0006] The resin material is selected from one or a combination of polyvinyl chloride, polyethylene, polypropylene and polystyrene;

[0007] The weight ratio of the resin material to the nano carbon powder is 10:2-5.

[0008] The present invention adds nano carbon powder with conductive function into the resin material. Studies have shown that the flexible heating film material containing nano carbon prepared by adding the nano carbon powder has certain heating performance.

[0009] Preferably, the weight ratio of the resin material to the nano-carbon powder is 10:3.

[0010] Preferably, the nano-carbon powder refers to nano-carbon powder with an average particle size of 20 to 100 nm.

[0011] Most preferably, the nano-carbon powder refers to nano-carbon powder with an average particle size of 50 nm.

[0012] Preferably, the nano-carbon powder is modified nano-carbon powder;

[0013] The modified nano carbon powder is prepared by the following method:

[0014] (1) adding nano-carbon powder into water and uniformly dispersing the nano-carbon powder by ultrasonication to obtain a modified nano-carbon powder dispersion;

[0015] (2) adding lutetium (III) sulfate octahydrate and yttrium (III) sulfate octahydrate to the modified nano-carbon powder dispersion and mixing them evenly, then adding sodium carbonate, stirring for 3 to 6 hours, and filtering and separating the solid;

[0016] (3) The solid separated in step (2) is calcined at 1500-1800° C. for 1-3 h; after the calcination, the calcined product is obtained to obtain the modified nano-carbon powder.

[0017] The inventors also found in further research that adding modified nano-carbon powder prepared by the above method to the resin material can further improve the heating performance of the prepared flexible heating film material containing nano-carbon, compared with adding unmodified nano-carbon powder.

[0018] In addition, the inventors surprisingly found in the study that adding modified nano-carbon powder prepared by the above method to the resin material can further significantly improve the gas barrier performance of the prepared nano-carbon-containing flexible heating film material compared to adding unmodified nano-carbon powder.

[0019] Preferably, in step (1), the weight ratio of nano carbon powder to water is 1:5-10.

[0020] Most preferably, the weight ratio of nano carbon powder to water in step (1) is 1:8.

[0021] Preferably, the nano-carbon powder described in step (1) refers to nano-carbon powder with an average particle size of 20 to 100 nm.

[0022] Most preferably, the nano-carbon powder described in step (1) refers to nano-carbon powder with an average particle size of 50 nm.

[0023] Preferably, in step (2), the weight ratio of the modified nano-carbon powder dispersion to lutetium (III) sulfate octahydrate, yttrium (III) sulfate octahydrate and sodium carbonate is 10: 0.05-0.1: 0.05-0.08: 0.08-0.12.

[0024] Most preferably, in step (2), the weight ratio of the modified nano-carbon powder dispersion to lutetium (III) sulfate octahydrate, yttrium (III) sulfate octahydrate and sodium carbonate is 10:0.08:0.06:0.1.

[0025] Preferably, the stirring in step (2) specifically refers to stirring for 5 hours.

[0026] Preferably, the solid separated in step (2) is calcined at 1700° C. for 2 h.

[0027] The present invention also provides a flexible heating film material containing nano-carbon prepared by the above preparation method.

[0028] Beneficial effects: The present invention provides a new method for preparing a flexible heating film material containing nanocarbon; studies have shown that the flexible heating film material containing nanocarbon prepared by the method of the present invention has a heating function after being powered on; the application scenarios of plastic films are broadened, so that films prepared with resin materials as raw materials can be used in fields with heating needs. DETAILED DESCRIPTION

[0029] The present invention is further explained below in conjunction with specific examples, but the examples do not limit the present invention in any form.

[0030] Example 1 Preparation of flexible heating film material containing nanocarbon

[0031] The polyethylene and nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0032] The weight ratio of polyethylene to nano-carbon powder is 10:3; and the average particle size of the nano-carbon powder is 50 nm.

[0033] Example 2 Preparation of flexible heating film material containing nanocarbon

[0034] The polyethylene and modified nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0035] Wherein, the weight ratio of polyethylene to modified nano carbon powder is 10:3;

[0036] The modified nano carbon powder is prepared by the following method:

[0037] (1) adding nano-carbon powder to water and uniformly dispersing the nano-carbon powder by ultrasonication to obtain a modified nano-carbon powder dispersion; wherein the weight ratio of the nano-carbon powder to water is 1:8; and the average particle size of the nano-carbon powder is 50 nm;

[0038] (2) adding lutetium (III) sulfate octahydrate and yttrium (III) sulfate octahydrate to the modified nano-carbon powder dispersion and mixing them evenly, then adding sodium carbonate, stirring for 5 hours, and filtering to separate the solid; wherein the weight ratio of the modified nano-carbon powder dispersion to the lutetium (III) sulfate octahydrate, the yttrium (III) sulfate octahydrate and the sodium carbonate is 10:0.08:0.06:0.1;

[0039] (3) The solid separated in step (2) is calcined at 1700° C. for 2 h; after the calcination, the calcined product is obtained to obtain the modified nano-carbon powder.

[0040] Example 3 Preparation of flexible heating film material containing nanocarbon

[0041] The polypropylene and the nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0042] The weight ratio of polypropylene to nano-carbon powder is 10:2; and the average particle size of the nano-carbon powder is 20 nm.

[0043] Example 4 Preparation of flexible heating film material containing nanocarbon

[0044] The polyvinyl chloride and the nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0045] The weight ratio of polyvinyl chloride to nano-carbon powder is 10:5; and the average particle size of the nano-carbon powder is 100 nm.

[0046] Example 5 Preparation of flexible heating film material containing nanocarbon

[0047] The polystyrene and the nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0048] The weight ratio of polystyrene to nano-carbon powder is 10:5; and the average particle size of the nano-carbon powder is 100 nm.

[0049] Example 6 Preparation of flexible heating film material containing nanocarbon

[0050] The polypropylene and modified nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0051] Wherein, the weight ratio of polypropylene to modified nano-carbon powder is 10:3;

[0052] The modified nano carbon powder is prepared by the following method:

[0053] (1) adding nano-carbon powder to water and uniformly dispersing the nano-carbon powder by ultrasonication to obtain a modified nano-carbon powder dispersion; wherein the weight ratio of the nano-carbon powder to water is 1:9; and the average particle size of the nano-carbon powder is 20 nm;

[0054] (2) adding lutetium (III) sulfate octahydrate and yttrium (III) sulfate octahydrate to the modified nano-carbon powder dispersion and mixing them evenly, then adding sodium carbonate, stirring for 3 hours, and filtering to separate the solid; wherein the weight ratio of the modified nano-carbon powder dispersion to the lutetium (III) sulfate octahydrate, the yttrium (III) sulfate octahydrate and the sodium carbonate is 10:0.05:0.08:0.12;

[0055] (3) The solid separated in step (2) is calcined at 1500° C. for 3 h; after the calcination, the calcined product is obtained to obtain the modified nano-carbon powder.

[0056] Example 7 Preparation of flexible heating film material containing nanocarbon

[0057] The polystyrene and the modified nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0058] Wherein, the weight ratio of polystyrene to modified nano-carbon powder is 10:5;

[0059] The modified nano carbon powder is prepared by the following method:

[0060] (1) adding nano-carbon powder to water and uniformly dispersing the nano-carbon powder by ultrasonication to obtain a modified nano-carbon powder dispersion; wherein the weight ratio of the nano-carbon powder to water is 1:5; and the average particle size of the nano-carbon powder is 100 nm;

[0061] (2) adding lutetium (III) sulfate octahydrate and yttrium (III) sulfate octahydrate to the modified nano-carbon powder dispersion and mixing them evenly, then adding sodium carbonate, stirring for 3 hours, and filtering to separate the solid; wherein the weight ratio of the modified nano-carbon powder dispersion to the lutetium (III) sulfate octahydrate, the yttrium (III) sulfate octahydrate and the sodium carbonate is 10:0.1:0.05:0.08;

[0062] (3) The solid separated in step (2) is calcined at 1600° C. for 2 h; after the calcination, the calcined product is obtained to obtain the modified nano-carbon powder.

[0063] Example 8 Preparation of flexible heating film material containing nanocarbon

[0064] The polyvinyl chloride and the modified nano-carbon powder are mixed evenly, and then melt-extruded through a twin-screw machine to obtain the flexible heating film material containing nano-carbon;

[0065] Wherein, the weight ratio of polyvinyl chloride to modified nano carbon powder is 10:4;

[0066] The modified nano carbon powder is prepared by the following method:

[0067] (1) adding nano-carbon powder to water and uniformly dispersing the nano-carbon powder by ultrasonication to obtain a modified nano-carbon powder dispersion; wherein the weight ratio of the nano-carbon powder to water is 1:7; and the average particle size of the nano-carbon powder is 80 nm;

[0068] (2) adding lutetium (III) sulfate octahydrate and yttrium (III) sulfate octahydrate to the modified nano-carbon powder dispersion and mixing them evenly, then adding sodium carbonate, stirring for 4 hours, and filtering to separate the solid; wherein the weight ratio of the modified nano-carbon powder dispersion to the lutetium (III) sulfate octahydrate, the yttrium (III) sulfate octahydrate and the sodium carbonate is 10:0.06:0.07:0.09;

[0069] (3) The solid separated in step (2) is calcined at 1550° C. for 3 h; after the calcination, the calcined product is obtained to obtain the modified nano-carbon powder.

[0070] The nanocarbon-containing flexible heating film material prepared in Examples 1 and 2 was made into a film with a thickness of 0.1 mm; the surface temperature of the film was tested after applying a 3.7 V direct current for 1 min; in addition, the oxygen permeability of the film was tested according to the method in GB / T 1038.1-2022 standard; the test results are shown in Table 1.

[0071] Table 1. Performance test results of flexible heating film materials containing nanocarbon

[0072]

[0073]

[0074] It can be seen from the experimental results in Table 1 that the film made of the flexible heating film material containing nanocarbon prepared in Example 1 has a temperature rising to 53°C after being heated by electricity; this shows that the flexible heating film material containing nanocarbon prepared by adding nanocarbon powder in the present invention has certain heating properties.

[0075] It can be seen from the experimental results in Table 1 that the temperature of the film made of the flexible heating film material containing nanocarbon prepared in Example 2 after being heated by electricity is significantly improved compared with the film made of the flexible heating film material containing nanocarbon prepared in Example 1; this shows that adding the modified nanocarbon powder prepared by the method of the present invention to the resin material can further improve the heating performance of the prepared flexible heating film material containing nanocarbon compared with adding unmodified nanocarbon powder.

[0076] It can be seen from the experimental results in Table 1 that the oxygen permeability of the film made of the flexible heating film material containing nanocarbon prepared in Example 2 is greatly reduced compared with the film made of the flexible heating film material containing nanocarbon prepared in Example 1; this shows that adding the modified nanocarbon powder prepared by the method of the present invention to the resin material can further greatly improve the gas barrier performance of the prepared flexible heating film material containing nanocarbon compared with adding unmodified nanocarbon powder.

Claims

1. A method for preparing a flexible heating film material containing nanocarbon, characterized in that: The method comprises the following steps: mixing the resin material and the nano-carbon powder evenly, and then melting and extruding the mixture through a twin-screw machine to obtain the nano-carbon-containing flexible heating film material; The resin material is selected from one or a combination of polyvinyl chloride, polyethylene, polypropylene and polystyrene; The weight ratio of the resin material to the nano carbon powder is 10:2-5.

2. The method for preparing a flexible heating film material containing nanocarbon according to claim 1, characterized in that: The weight ratio of the resin material to the nano-carbon powder is 10:

3.

3. The method for preparing the flexible heating film material containing nanocarbon according to claim 1 is characterized in that: The nano carbon powder is a nano carbon powder with an average particle size of 20 to 100 nm. Most preferably, the nano-carbon powder refers to nano-carbon powder with an average particle size of 50 nm.

4. The method for preparing the flexible heating film material containing nanocarbon according to claim 1 is characterized in that: The nano carbon powder is modified nano carbon powder; The modified nano carbon powder is prepared by the following method: (1) adding nano-carbon powder into water and uniformly dispersing the nano-carbon powder by ultrasonication to obtain a modified nano-carbon powder dispersion; (2) adding lutetium (III) sulfate octahydrate and yttrium (III) sulfate octahydrate to the modified nano-carbon powder dispersion and mixing them evenly, then adding sodium carbonate, stirring for 3 to 6 hours, and filtering and separating the solid; (3) The solid separated in step (2) is calcined at 1500-1800° C. for 1-3 h; after the calcination, the calcined product is obtained to obtain the modified nano-carbon powder.

5. The method for preparing a flexible heating film material containing nanocarbon according to claim 4, characterized in that: In step (1), the weight ratio of nano carbon powder to water is 1:5-10. Most preferably, the weight ratio of nano carbon powder to water in step (1) is 1:

8.

6. The method for preparing a flexible heating film material containing nanocarbon according to claim 4, characterized in that: The nano carbon powder described in step (1) refers to nano carbon powder with an average particle size of 20 to 100 nm. Most preferably, the nano-carbon powder described in step (1) refers to nano-carbon powder with an average particle size of 50 nm.

7. The method for preparing a flexible heating film material containing nanocarbon according to claim 4, characterized in that: In step (2), the weight ratio of the modified nano-carbon powder dispersion to lutetium (III) sulfate octahydrate, yttrium (III) sulfate octahydrate and sodium carbonate is 10: 0.05-0.1: 0.05-0.08: 0.08-0.

12. Most preferably, in step (2), the weight ratio of the modified nano-carbon powder dispersion to lutetium (III) sulfate octahydrate, yttrium (III) sulfate octahydrate and sodium carbonate is 10:0.08:0.06:0.

1.

8. The method for preparing a flexible heating film material containing nanocarbon according to claim 4, characterized in that: The stirring described in step (2) specifically refers to stirring for 5 hours.

9. The method for preparing a flexible heating film material containing nanocarbon according to claim 4, characterized in that: The solid separated in step (2) was calcined at 1700° C. for 2 h.

10. A flexible heating film material containing nanocarbon prepared by the preparation method according to any one of claims 1 to 9.